CARBONATE FACIES AND DEPOSITIONAL ENVIRONMENT DEVELOPMENT IN BAYAH AREA AND GUNUNG WALAT, ITS RELATIONSHIP WITH OLIGO-MIOCENE TECTONIC ACTIVITY IN WEST JAVA - Mk Hainim, Iwan
Oligo-Miocene age limestones are exposed in several locations in Western Java, known as the Rajamandala Formation, Citarate Formation and Saraweh Formation. This limestone is also one of the important oil and gas reservoirs in the northern part of West Java. On the surface, this limestone is exposed in the Padalarang area, Sukabumi, Gunung Walat, to Bayah on the south coast. In the Bayah area, this Oligo-Miocene limestone is exposed around the Bayah plateau, known as the Upper Cijengkol and Citarate Formation. While in the Sukabumi area, this limestone is called the Rajamandala Formation. Several oil and gas wells drilled in the central part of western Java, precisely in the Rangkas area, this OligoMiocene aged limestone was also found, equated with the Saraweh Formation. To find out more about the distribution pattern of these limestones, research needs to be done, whether these limestones grow in ancient highland areas, or grow around volcanic morphology. The research was conducted using field data in the Bayah and Gunung Walat - Sukabumi areas. For field research, the focus was on Oligo-Miocene limestone, micro facies approach, facies association and determination of depositional environment. The study methods were outcrop observation and petrographic analysis. Foraminifera biostratigraphic analysis was conducted to determine the age and depositional environment. In addition to using surface data, the research also used subsurface data in the form of seismic data and gravity data. Especially for seismic analysis using data from the area around Rangkasbitung. From the petrographic analysis of rock samples from the Bayah area, 14 micro facies. These facies associations integrated with the results of biostratigraphy analysis indicate depositional environments: intra reef, lagoon, back reef, reef core, fore reef, fore slope, slope and upper bathyal. The ages for these rocks are P22 and Te4 (Late Oligocene) and N4 (Early Miocene). As for the Gunung Walat – Sukabumi area, 8 micro facies can be distinguished. This facies association integrated with the results of biostratigraphy analysis indicates depositional environments: intra reef, shoal, shelf, back reef, reef core, fore reef, slope and upper bathyal. The age of this limestone is P22 (Late Oligocene) to N4 (Early Miocene) and Te1-Te3 to Te4 (letter stage). The limestone outcropped parallel with Cimandiri Fault direction, east north east – west south west in that particular area. From the stratigraphic position, the Rajamandala limestones exposed near Sukabumi (Karang Para, Karang Numpang) are directly above the Eocene-aged Walat/Bayah sandstones with unconformable contacts. Whereas in the west, the Rajamandala Formation limestones overlie unconformably the P19 age Batuasih Formation shale. The depositional environment of limestone in Bayah shows that shallower depositional environments, platform interior (lagoon, back reef, reef core, intra reef) are located in the west south west, while towards the east – north east the limestone changes facies to deposits with deeper environments (slope, deep shelft and basinal). The position of this depositional environment indicates that the limestone growth has a north west – south east to north-south polarity. As for Sukabumi, limestone development always starts with the back reef and shoal environments, then moves upwards to reef core and intra reef. Seismic analysis shows that the sedimentary basin in the study area was formed due to an extension process into a rift basin with strike-slip influence that formed a horst and graben and flower structure. There is a change in the fault orientation pattern, in the deeper layers (Basement and Bayah Formation Equivalent) the direction is almost north-south, while in the shallower layers the direction is southwest-northeast to west-east. This change in fault orientation is followed by a change in the direction of the long axis of the depocenter, and also the location of the depocenter itself is shifted. The limestone of the Saraweh Formation can be identified, especially along the ancient highlands, the body of a reef is clearly visible, with clastic sediments onlapping on the reef side. The gravity analysis can identify 3 structural alignment patterns, namely the southwest-northeast direction (Meratus / Cimandiri pattern) of Late Cretaceous - Paleocene age, north-south direction (Eocene), northwest-southeast direction (Sumatra direction, Oligocene - Miocene). Oligo-Miocene aged limestones are seen to grow following the alignment pattern of this structure. The polarity of limestone in the Bayah area is northwest - southeast, following the existing-structure direction of Sumatra, while in the Sukabumi area the polarity of limestone is west - east, following the direction of the Cimandiri Fault in that area (Meratus Pattern), and in the Rangkas area the limestone develops along a north-south oriented highland. Gravity analysis revealed that the Rangkas Basin is separated from the Bogor Basin. Palinspastic and strain analysis indicate the existence of tectonic activity with an extensional regime in the Eocene age in West Java, which occurred due to a slowdown in the subduction rate. Basins were formed that were filled by terrestrial to transition sediments, this activity part of syn-rift period. In the Late Oligocene, tectonic activity was relatively stable, entering the post-rift and sagging period, Oligo-Miocene aged limestones were deposited. In the Early Miocene, tectonic activity increased, contractional regime occurred, magmatic arcs formed along Java accompanied by thrust faults, the Bogor basin deepened, the limestone of the Rajamandala Formation drowned and was covered by younger rocks which were submarine fan deposits. From the surface and subsurface data, the Oligo-Miocene age limestone growth is spread from the Bayah area in the south, towards the Rangkas area and continues off the coast of Java in the north. To the east, this limestone is exposed up to Padalarang. The Oligo-Miocene limestones in the Bayah area are located within the Late Eocene - Early Miocene magmatic arc zone, while the Oligo-Miocene limestones in Sukabumi are located on the edge of the back arc. The wide distribution can be concluded that during the Oligo-Miocene Period, western Java was a shallow sea where limestones grew on ancient highs, in the south the influence of morphology formed by volcanic activity (Old Andesite) along the highs also influenced the growth of limestones.